B cell and anti-PLA2R antibody-guided rituximab therapy in idiopathic membranous nephropathy: a prospective multi-center cohort study in the East Coastal Region of China - Xu, Yili; Wang, Liang; Jiang, Chunming; Sun, Dong; Yang, Min; Liu, Jin; Liu, Xiaobin; Wan, Cheng; Liu, Caixia; Zhang, Bo; Bi, Guangyu; Chen, Lianhua; et al. (Frontiers in Immunology, 2025)
IntroductionThis study assessed the safety and efficacy of B cell- and anti-PLA2R antibody-targeted low-dose rituximab therapy in patients with idiopathic membranous nephropathy (IMN).MethodsThis was a multicenter, investigator-initiated, open-label, prospective cohort study. Patients were recruited from 10 hospitals in the east coastal region of China between November 1st, 2019 and June 15th, 2023. Enrolled patients were assigned to individualized rituximab therapy (guided by peripheral B cells and anti-PLA2R antibody levels) or standard rituximab therapy (1,000 mg × 2 or 375 mg/m² × 3–4): the individualized group (n = 78) and the standard group (n = 62). Odds ratios (ORs) and 95% confidence intervals (CIs) for response were estimated using multivariate logistic regression models, adjusting for key confounders, with inverse probability of treatment weighting (IPTW) applied to balance demographic and clinical characteristics. The primary outcome was a composite of complete or partial remission of proteinuria.ResultsA total of 140 patients were included in the sta tistical analysis, which was completed on June 10th, 2024. After IPTW, baseline characteristics were well balanced between the two groups. Patients were followed every 2 months for 1 year after the first rituximab injection. At 12 months, 57 of 78 patients (73.1%) in the individualized therapy group and 40 of 62 patients (64.5%) in the standard therapy group achieved complete or partial remission [the adjusted risk difference and 95% CI were 0.1 (–0.05 to 0.26); p = 0.001 for noninferiority]. In the weighted cohort, 74.1% in the individualized group and 70.5% in the standard group achieved remission (p = 0.5). The median (interquartile range) total rituximab dose per patient at 1 year was 800 mg (600–1,100 mg), with a total cost of RMB 16,227.5 (13,148–23,536) per unit utility in the individualized group, which was markedly lower than in the standard group. Anti-PLA2R autoantibody negativity at 6 months post-treatment predicted a higher probability of remission. The frequency of adverse events differed significantly between groups (6.4% vs. 12.9%, P = 0.02).DiscussionB cell- and anti-PLA2R antibody-targeted rituximab therapy may be a cost-effective and safe alternative for patients with IMN. Randomized controlled trials with larger samples are needed to confirm these findings.Clinical Trial Registrationhttps://www.chictr.org.cn/showproj.html?proj=42793, identifier ChiCTR1900026382.